Nanotechnology and nanoscaled materials for microsystems application - Mladlenov, Georgiy; Koleva, Elena; Yakymenko, Yuriy; Spivak, Viktor; Bogdan, Oleksandr; Orlov, Anatoliy (Видавництво Львівської політехніки, 2010)
stages of formation and some perspective aspects of nanotechnology development, in particular, nanoelectronics, getting nanomaterials and microsystems device is analyzed in this report.
Keywords: anoelectronics; synthesis Of Nanostructure; electronic and Ion Lithographic; thin Tapes; microsystems; resonators; piezoelectrics Device